2001
DOI: 10.1002/poc.365
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of carbon dioxide radical anion with substituted benzenes

Abstract: We report mechanistic studies on the reactivity of CO 2 .À radicals towards substituted benzenes, XPh, with X = NO 2 , COOH, COH, CH 3 , H, Cl and HO. Vacuum ultraviolet (VUV, 172 nm) irradiation of aqueous solutions containing formate was used as a method of CO 2 .À radical generation for the study of the reaction products, which were determined by gas chromatography-mass spectrometry and high-performance liquid chromatography. The nature of some of the reaction intermediates was studied by laser flash photol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…Peroxodisulphate photolysis in Ar-saturated solutions containing formate yields CO 2 + ( radical anions, reaction R4 [15], which were reported to reduce A.H 2 O to AH + radicals, R12 [11,17]. In the presence of molecular oxygen, CO 2 + ( efficiently reacts with O 2 to yield superoxide radical anions, O 2 + ( , R6, which are also reported to reduce A.H 2 O to AH + radicals, R13a [18].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Peroxodisulphate photolysis in Ar-saturated solutions containing formate yields CO 2 + ( radical anions, reaction R4 [15], which were reported to reduce A.H 2 O to AH + radicals, R12 [11,17]. In the presence of molecular oxygen, CO 2 + ( efficiently reacts with O 2 to yield superoxide radical anions, O 2 + ( , R6, which are also reported to reduce A.H 2 O to AH + radicals, R13a [18].…”
Section: Resultsmentioning
confidence: 95%
“…These radicals efficiently react with formate ions to yield carbon dioxide radical anions (CO 2 + ( ), which in the presence of molecular oxygen are quantitatively converted into O 2 + ( [15].…”
Section: Methodsmentioning
confidence: 99%
“…It has been documented that the carbonate radical (CO 2 ÅÀ ) can be generated from HCO 4 À [30]. In addition, it has been reported that CO 2 ÅÀ can degrade benzene by both addition and H-abstraction mechanisms [31]. Hence, we speculate that a large number of other active species (such as HCO 4 À and CO 2 ÅÀ ) make the contribution of the apparent expediting effect when the HCO 3 À concentration is increased from 10 to 100 mM.…”
Section: Ion Effectmentioning
confidence: 99%
“…In spite of all our efforts, we could not find any studies considering the effects of CO 2 -addition to benzene during the combustion of the latter. Rosso et al [71] investigated the reaction of carbon dioxide radical anion with substituted benzenes in aqueous solutions. There does not appear to be any direct connections between their results and our main concerns in this article.…”
Section: Adiabatic Combustion Without the Kinetics Of Comentioning
confidence: 99%